Aversive societal conditions explain differences in “dark” personality across countries and US states - Ingo Zettler; Lau Lilleholt; Martina Bader; Benjamin E. Hilbig; Morten Moshagen (Proceedings of the National Academy of Sciences, 2025)
Humans differ in their levels of aversive (“dark”) personality traits such as egoism or psychopathy. Building upon theories suggesting that socioecological factors coshape the development of personality traits, it can be predicted that prior aversive societal conditions (ASC) (herein assessed via corruption, inequality, poverty, and violence) explain individuals’ levels of aversive personality (assessed via the Dark Factor of Personality, the common core underlying all aversive traits). Results considering individuals from 183 countries ( N = 1,791,542) and 50 US states ( N = 144,576) support the idea that ASC coshape individuals’ levels of aversive personality.